The Ghost Story 1840-1920 : a cultural history. - Smith, Andrew, 1964- (Manchester University Press, 2010)
The Ghost Story 1840-1920: A Cultural History examines the British ghost story within the political contexts of the long nineteenth century. By relating the ghost story to economic, national, colonial and gendered contexts' it provides a critical re-evaluation of the period. The conjuring of a political discourse of spectrality during the nineteenth century enables a culturally sensitive reconsideration of the work of writers including Dickens, Collins, Charlotte Riddell, Vernon Lee, May Sinclair, Kipling, Le Fanu, Henry James and M.R. James. Additionally, a chapter on the interpretation of sp.